An investigation of the mediating role of personality and family functioning in the association between attachment styles and eating disorder status. Issue 1 (December 2016) - Münch, Anna; Hunger, Christina; Schweitzer, Jochen
Abstract Background This study examined relationships between attachment style, eating disorders (EDs), personality variables and family functioning. Methods In our study, 253 women (M = 25.72 years, SD = 8.73) were grouped into one of four categories either according to self-reported ED diagnosis or by exceeding cut-offs for a clinical diagnosis on theEating Disorder Examination Questionnaire (EDE-Q) orShort Evaluation of Eating Disorders (SEED) : anorexia nervosa (AN), bulimia nervosa (BN), other eating disorder (O-ED), no eating disorder (Non-ED). The ED group (AN, BN, O-ED) included 106 women (M = 24.74 years, SD = 7.71), and the Non-ED group 147 women (M = 26.42 years, SD = 9.37). Approximately half of the ED group had a comorbid disorder (59.4 %), while the majority of the Non-ED group had no psychological disorder (89.1 %). Results Participants with an ED were significantly more often insecurely attached (Adult Attachment Scale; AAS), emotionally unstable, less extraverted (Big-Five-Test of Personality; B5T) and showed less positive family functioning (Experiences in Personal Social Systems Questionnaire; EXIS.pers ). Results showed partial mediation for attachment and EDs through neuroticism, extraversion and family functioning. Discussion The study found further evidence for elevated problems with attachment, personality, and family experiences in individuals with EDs, while suggesting mechanisms that may link these constructs. Implications for research and practice were discussed. Conclusion This study supports findings that acknowledge the mediating role played by personality factors and family functioning in the relationship between attachment and EDs.